The Effect of Exercise on Weight Changes in Obese Nursing Students of Santa Elisabeth College of Health, Medan - Imelda Derang; Oktaviance Simorangkir; Paskah Ramawati (Postgraduate, University of Mataram, 2025)
Exercise is physical exercise for fitness and health. There are several types of exercise including jogging, cycling, swimming and dancing. Zumba dance is a physical activity with Latin dance movements and can help burn calories aimed at fitness and health, especially for people who are overweight (obesity) which is characterized by excessive fat accumulation due to an imbalance between energy in and energy out. This will have an impact on health and result in various chronic diseases. This study aims to analyze whether there is an influence of Zumba Dance on weight loss for students in the Nursing Study Program. Quantitative research type with a pre-experimental design using one group pretest-posttest design, total sampling technique with a total sample of 27 respondents. The instrument used is the observation sheet. After doing Zumba Dance, there was a weight loss of 27 people (100%), the Wilcoxon Sign Rank Test statistical test obtained p value= 0.001 (p<0.05) which means there is a significant influence between Zumba dance on weight loss in the nursing student program at the Santa Elisabeth College of Health Sciences who was obese. It is hoped that you will continue to do Zumba dance to maintain body weight balance, increase fitness and health, while maintaining a healthy diet